2020
DOI: 10.1002/eat.23219
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on the link between weight‐related self‐stigma and binge eating: Role of food addiction and psychological distress

Abstract: Objectives This prospective study investigated the link between weight‐related self‐stigma and binge eating by (a) examining the temporal association between weight‐related self‐stigma and binge eating; (b) investigating the mediating role of food addiction in the association between weight‐related self‐stigma and binge eating; and (c) examining the mediating role of psychological distress in the association between weight‐related self‐stigma and binge eating. Method Participants comprised 1,497 adolescents (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 56 publications
(95 reference statements)
0
44
0
Order By: Relevance
“…Kappa for the abstract review was 0.88 (95% CI; 0.77–0.98), and Kappa for the full text review was 0.92 (95% CI; 0.84–0.99). All 22 studies were cross‐sectional 24,28–48 . No longitudinal studies were identified in the search.…”
Section: Resultsmentioning
confidence: 99%
“…Kappa for the abstract review was 0.88 (95% CI; 0.77–0.98), and Kappa for the full text review was 0.92 (95% CI; 0.84–0.99). All 22 studies were cross‐sectional 24,28–48 . No longitudinal studies were identified in the search.…”
Section: Resultsmentioning
confidence: 99%
“…Weight‐related teasing by parents and peers is associated with binge eating and purging behaviors, body shame, and disordered eating 47–49 . This association between weight‐related stigma and binge eating may be mediated by psychological distress in adolescents 50 …”
Section: Eating Disorder Risk Factors In Adolescents and Obesitymentioning
confidence: 99%
“…Investigating whether modifiable risk factors such as eating disorder attitudes, food addiction, and insomnia are mediators in the relationship between psychological distress and excess weight may help identify important targets for treatment. Although prior studies by the present authors [35,36] have found other psychopathological mechanisms that explain the mediating roles of food addiction, psychological distress, and insomnia for adolescents who are overweight, none of the studies investigated the mechanism explaining the outcome of gaining excess weight. More specifically, Lin et al [35] investigated on the outcome of quality of life and Ahorsu et al [36] on binge eating disorder.…”
Section: Introductionmentioning
confidence: 81%
“…Although prior studies by the present authors [35,36] have found other psychopathological mechanisms that explain the mediating roles of food addiction, psychological distress, and insomnia for adolescents who are overweight, none of the studies investigated the mechanism explaining the outcome of gaining excess weight. More specifically, Lin et al [35] investigated on the outcome of quality of life and Ahorsu et al [36] on binge eating disorder. The outcome of the present study was decreasing, maintaining, or increasing excess weight among Iranian adolescents who were overweight, and the findings will be useful for healthcare providers, especially because such topics are understudied among Iranian adolescents.…”
Section: Introductionmentioning
confidence: 81%